Kikuchi–Fujimoto disease: A rare cause of cervical lymphadenopathy - Shaju, Reshma Mariya; Kumar, Adarsh S; Joseph, Susy; Kiran, N; Ajithkrishnan, AS (Indian Journal of Case Reports, 2024)
Kikuchi–Fujimoto disease (KFD), also known as histiocytic necrotizing lymphadenitis, is a rare and generally self-limiting disease of uncertain etiology that presents with fever and cervical lymphadenopathy in both the pediatric and adult populations. Here, we present the case of a 5-year-old male who presented with acute onset of fever and cervical lymphadenopathy which was initially diagnosed and managed as staphylococcal lymphadenitis. He underwent an excisional biopsy when symptoms persisted, which confirmed the diagnosis of KFD and was managed conservatively. This case study emphasizes awareness of this entity in the differential diagnosis of fever with persistent lymphadenopathy. Due to its characteristic overlap with other disorders such as tuberculous lymphadenitis, and lymphoma, KFD remains an arduous diagnosis for physicians. Therefore, awareness about its symptoms helps in minimizing potentially harmful unnecessary evaluations and thereby preventing misdiagnosis and inappropriate treatment.